Clinical Efficacy of Muscle Energy Technology Combined with Conventional Rehabilitation Therapy on Patients with Chronic Non-Specific Neck Pain - ZHENG Kun; YANG Haolun; JIA Chengsen; ZHANG Liming (康复学报)
ObjectiveTo observe the effects of muscle energy technology (MET) combined with conventional rehabilitation trerapy on patients with chronic non-specific neck pain (CNSNP).MethodsA total of 54 patients with CNSNP in the outpatient department of rehabilitation medical center of West China Hospital, Sichuan University from May 2022 to March 2023 were randomly divided into control group and observation group, with 27 cases in each group. During the course of treatment, three cases withdrew from the study due to poor compliance, including two cases in the control group and one case in the observation group. Finally 25 and 26 cases were included in the control group and the observation group, respectively. The control group received conventional rehabilitation trerapy (physical modality therapy and exercise training) combined with stretching training. Physical modality therapy mainly included magnetothermal therapy and medium frequency pulsed electrotherapy, with a duration of 20 minutes a time for each treatment, once a day, continuous treatment, and three times a week; exercise training included isometric contraction training and deep neck flexor muscle group training, with three times a day, continuous treatment, and three times a week; stretching training were performed once a day, continuous treatment, and three times a week. The observation group received MET therapy in addition to the conventional rehabilitation therapy in the control group. The therapist stretched the target muscle to the position where pain was triggered or the resistance point of soft tissue could be felt, fixed the starting and ending points of the muscle with both hands, applied moderate resistance, and allowed the patient's target muscle to perform isometric contraction (an intensity of 20% of the maximum force) and relax after 10 seconds, and then continued to stretch the target muscle and reached the position of the next resistance point, taking the resistance point as the starting position, repeated the procedure 3 to 5 times, once a day, three times a week, lasting for one week. Before treatment and one week after treatment, visual analog scale (VAS) was used to assess the pain level; neck disability index (NDI) was used to evaluate cervical spine dysfunction; Yasuhisa Tanaka cervical spondylotic radiculopathy 20 (CSR20) was used to evaluate cervical spine function; "Clinical practice guideline for physical therapy assessment and treatment in patients with nonspecific neck pain" were used to evaluate the clinical efficacy; the adverse reaction such as aggravation of neck pain, nausea, vomiting, dizziness, increased heart rate, etc. that occurred during treatment were observed.ResultsCompared with that before treatment, VAS scores and NDI index decreased significantly of both groups after treatment (P<0.05), CSR20 score increased significantly, and the differences were statistically significant (P<0.05). Compared with the control group, VAS score was significantly lower in the observation group after treatment, CSR20 score was significantly higher, and the differences were statistically significant (P<0.05). The effective rate in the observation group (92.31%) was higher than that of the control group (28.00%), and the difference was statistically significant (P<0.05). During the course of treatment, there were no adverse reactions in both groups.ConclusionMET combined with conventional rehabilitation therapy can effectively improve the pain and cervical spine function of patients with CNSNP, which is recommended for clinical promotion and application.